THE USAGE OF LEARNING ROOTS FOR INFORMATION SCIENCE COURSES IN MAHASARAKHAM UNIVERSITY, THAILAND - Phornphatcharaphong, Wilawan (Malaysian Journal of Library and Information Science, 2003)
Describes the use of learning root for Information Science undergraduate courses in Mahasarakham University, Thailand in terms of content, delivery, access, interaction, and assessment. This is an experimental research using Web-Based Instruction (WBI). A total of 244 questionnaires (97.21%) were analyzed. The results reveals that firstly, most students enter the root through the Language course, the students use the learning root in various styles, for example, students who study Computer and Business always spent more time with courseware module, the students who study Language and Internet enjoy reading magazine whereas the students who study Information Industry like to read about publishing. Secondly, most students agree that the content can be placed in server and delivered from website named noc.rimhk.ac.th/aom. Thirdly, most students access the learning root from their department’s laboratory. The students in Languages course show more interaction by writing on electronic board to ask how to use webpage. Students score pass at 50% from the quiz, the traditional assessment after using learning root. The important problem of learning root is the format of web pages that are chosen.